2023
DOI: 10.1021/acs.jmedchem.3c00382
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pH-Responsive Peptide–Paclitaxel Conjugate as a Novel Drug with Improved Therapeutic Potential

Abstract: A highly sensitive, nontoxic, hydrophilic cell-penetrating peptide (CPP = c[RGDKLAK]) was selected for the construction of an effective peptide−drug conjugate (PDC). A hydrophobic drug paclitaxel (PTX) was successfully conjugated with CPP via ester linkage with succinic acid (SA) as a pH-cleavable linker moiety. The characterization techniques employed in this study indicate the >95% purity of the resulting PDC (CPP−SA−PTX). The in vitro studies show that our proposed PDC exhibits enhanced stability (∼90%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, Rizvi et al for the first time reported the synthesis of synergistic cell-penetrating peptide (cRGD-KLAK) conjugated with paclitaxel via ester linkage with succinic acid as cleavable linker. The proposed PDC was observed to possess improved solubility in water, enhanced stability in blood circulatory system (≥90%), as well as promising tumor-growth inhibitory effect (2.82–3.24-folds) in glioblastoma models …”
Section: Peptides For Delivery Cargoes Through Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Rizvi et al for the first time reported the synthesis of synergistic cell-penetrating peptide (cRGD-KLAK) conjugated with paclitaxel via ester linkage with succinic acid as cleavable linker. The proposed PDC was observed to possess improved solubility in water, enhanced stability in blood circulatory system (≥90%), as well as promising tumor-growth inhibitory effect (2.82–3.24-folds) in glioblastoma models …”
Section: Peptides For Delivery Cargoes Through Bbbmentioning
confidence: 99%
“…The proposed PDC was observed to possess improved solubility in water, enhanced stability in blood circulatory system (≥90%), as well as promising tumor-growth inhibitory effect (2.82−3.24-folds) in glioblastoma models. 51 Furthermore, Ryppa et al reported the conjugation of divalent RGD (E-[c(RGDfK) 2 ]) with DOX through cleavable metalloproteinase-2/9-octapeptide, which shows significant drug release in tumor-microenvironment compared to their amide linker-based construct. 153 Another group coupled the 3′-amino position of DOX with the free carboxylic group of RGD-4C analog via amide linkage and found that this PDC exhibits enhanced inhibitory tumor growth and metastasis rate as compared to free DOX.…”
Section: ■ Peptides For Drug Delivery Systemmentioning
confidence: 99%
“…[62] In a recent study, succinic acid (SA) was used as an acid cleavable linker to conjugate hydrophobic drug paclitaxel (PTX) with cell-penetrating peptide (CPP) resulting a pH-cleavable connecting conjugate. [69] In vitro stability experiments were conducted in 1x PBS (pH 7.4), freshly isolated mouse serum proteins, and complete cell culture medium (IMDM + 10 % FBS), respectively. The results showed that the conjugate exhibited greater stability in all three media (> 90 %, R t = 6.541 min) compared to free PTX.…”
Section: Acid Cleavable Linkermentioning
confidence: 99%
“…Therefore, we discuss here only the most widely linkage systems for peptide-drug conjugates with some recently published examples (Table 1). O-N acyl shift [22][23][24] Hydrazone -CO-NH-N=C--CO-NH-NH2 + O=C< bond formation by chemo-selective ligation; free drug release at pH < 5 (in lysosomes)…”
Section: Linker Systemsmentioning
confidence: 99%